Analisis Kecenderungan Survival Penderita HIV (+) dengan Terapi ARV Menggunakan Aplikasi Life Table - Munfaridah Munfaridah; Diah Indriani (Universitas Airlangga, 2016)
Survival analysis was a technique in statistical that used to analyze the data of an event, starting from the beginning to the end of the event and noted the timing of the events that have been determined, time was recorded in a day, week, month, or year. The purpose of this research was analyzed tendency survival with HIV positive of stage III to clinical stage AIDS. This research method used analytic observational with retrospective cohort design, analysis data used descriptive analysis and analysis of life table survival. The research used units of data population with inclution criteria, the first diagnosed with HIV (+) stage III at Dr. Kariadi Semarang Hospital from year 2008–2012, CD4 less from 200 sel/mm3 and consumed antiretroviral. The results showed a tendency survival of patients with HIV faster have been AIDS are low educational status 10 months, faster than on the status of higher education with decreased survival of 50%; the age group over 40 years, faster of 35 months less than the age group less 40, with years with decreased survival of 25%; HIV patients who started antiretroviral therapy with low CD4 counts, faster 7.5 months had been AIDS at the start of antiretroviral therapy with CD4 high, the chances of survival decrease by 60%. Early detection of HIV must be done in order to support the prevention of AIDS.